Analysis of the flexibility profile in young taekwondo athletes (Revista de Artes Marciales Asiáticas, 2018)
The main aim of this study was to determine the flexibility profile of the lower extremity in young taekwondo athletes, as well as identifying athletes with muscle shortness. For this purpose, a total of 17 young taekwondo athletes were assessed; seven from the Spanish team and ten from the Murcia team. The range of motion of the main movements of the lower extremity was evaluated by the "ROM SPORT" protocol and a descriptive analysis of each of the quantitative variables was performed. A Student t-test or arWilcoxon test was applied depending on the normality distribution of the data. The ROM values of each movement were classified as “normal” or “shortness” according to previously determined reference values. The results define the following flexibility profile: 23º for iliopsoas, 28º for piriformis, 37º for gastrocnemius, 42º for soleus, 46º for adductors, 46º for external rotators, 56º for internal rotators, 77º for monoarticular adductors, 80º for hamstrings, 140º for quadriceps and 145º for gluteus maximus. Individual evaluations identified muscle shortness in pyramidal (11 athletes, 64.7%), soleus (13 athletes, 76.4%), external rotators (8 athletes, 47%), monoarticular adductors (14 athletes, 82.3%), hamstrings (13 athletes, 76.4%), quadriceps (4 athletes, 23.5%) and gluteus maximus (12 athletes, 70.5%). This flexibility profile can help sports professionals to set quantifiable goals for the training of flexibility in this sport. The inclusion of stretching exercises or the increase of their doses should be applied for the improvement of the identified shortness in piriformis, soleus, external hip rotators, monoarticular, hamstring, quadriceps and gluteus maximus adductors.